BREED EFFECT ON MILK AMINO ACIDS PROFILE OF SELECTED INDIGENOUS BREEDS OF CATTLE IN NIGERIA - Abbaya, Yohanna, Hassan; Jechoniah, mamiso, B; Dauda, A.; Adamu, J.; Dubagari, N. G. (FUDMA JOURNAL OF SCIENCES, 2022)
Milk from the indigenous breeds in Nigeria is the most consumed by the populace. The certainty of the quality of the milk produced from this traditional pastoralists in Nigeria are unknown to most consumers. This work aimed at investigating the differences caused by breeds on the amino acid constituents of the milk of four breeds of cattle (Red Bororo, Adamawa Gudali, White Fulani and Sokoto Gudali) in Mubi. A total of eighty (80) milk samples (20 each per breed) were collected and analyzed for amino acids profile. The result indicated a significant(P<0.05) effect of breed on means of Lysine, Methionine, Isoleucine, phenylalanine, Valine, Tryptophan, Tyrosine, Aspartic acid and Glutamic acid while Threonine, Leucine, Histidine, Arginine, Serine, Cysteine, Alamine, Glycine and Proline were not significantly (P>0.05) affected by the breed. White Fulani recorded the highest in Glutamic acid, Red Bororo recorded the highest in Isoleucine), Valine, Tryptophan while Adamawa Gudali had the highest in Phenylalanine. Principal component (PC) 1 and 2 in each of the breeds accounted for over 90% percent cumulative variance suggesting that most of the amino acids in the milk of cows studied are varied within PC1 and PC2. There is no significant (p>0.05; r = -0.10 – 0.22) correlation between lysine with threonine, phenylalanine and serin and glutamic acid; valine with aspartic acid; threonine with valine and glutamic acid but a perfect correlation (p<0.001: r = 1.00) exist between tryptophan with isoleucine; histidine with glycine and valine with cysteine. It is therefore concluded